Haemophilus influenzae type b disease in the Oxford region. Issue 4 (April 1989) - Tudor-Williams, G; Frankland, J; Isaacs, D; Mayon-White, R T; MacFarlane, J A; Slack, M P; Anderson, E; Rees, D G; Moxon, E R
Abstract : A prospective survey of children in the Oxford region identified 200 cases of systemic Haemophilus influenzae type b disease in the first three and a half years of the study. The annual incidence in children less than 5 years of age was 33.4/100, 000. This represents a cumulative incidence of one systemic infection in 600 children before their 5th birthday. The mortality was 5.0%. The risk of H influenzae type b meningitis was one in 850 with a mortality of 5.6%, and substantial morbidity among survivors. From the total live birth rate, about 1300 cases of systemic H influenzae type b disease, over 900 cases of H influenzae type b meningitis, and 65 deaths would be predicted annually in children in the United Kingdom.